Neodeightonia arengae sp. nov., Botryosphaeriaceous taxa on Arenga tremula (Arecaceae) from Guangdong, China - Xiong, Yinru; Manawasinghe, Ishara S.; Liao, Chunfang; Hyde, Kevin D.; Dong, Zhangyong (Phytotaxa, 2022)
Microfungi associated with palm are a significant fungal group with a unique ecological niche and a broad distribution in tropical regions. Even though many fungal species have been reported from palm hosts, studies on fungi from Arenga tremula are considerably few. In this study, we isolated a saprobic Botryosphaeriaceae species on A. tremula, collected from Guangzhou, Guangdong Province, China. Morphological characteristics and phylogenetic analysis of the internal transcribed spacer (ITS), small subunit nuclear rRNA gene (SSU),part of the large subunit nuclear rRNA gene (LSU) and translation elongation factor 1−alpha gene (tef 1-α). Based on phylogenetic results and morphology we introduced Neodeightonia arengae sp. nov., with species description and illustrations. In addition, we provide a comparison of morphological characters of currently accepted Neodeightonia species. This is the first report of a Neodeightonia species associated with Arenga tremula and so represents an additional contribution to the knowledge of fungi associated with palm trees.